2017
DOI: 10.1002/2017ja024730
|View full text |Cite
|
Sign up to set email alerts
|

How Much Flux Does a Flux Transfer Event Transfer?

Abstract: Flux transfer events are bursts of reconnection at the dayside magnetopause, which give rise to characteristic signatures observed by a range of magnetospheric/ionospheric instrumentation. One outstanding problem is that there is a fundamental mismatch between space‐based and ionospheric estimates of the flux that is opened by each flux transfer event—in other words, their overall significance in the Dungey cycle. Spacecraft‐based estimates of the flux content of individual flux transfer events (FTEs) correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 109 publications
6
62
0
1
Order By: Relevance
“…Since the size of Mercury's polar cap is estimated to be about 4–6 MWb (Alexeev et al, ), this would suggest that an individual FTE could open flux corresponding to ∼1–5% of the open flux content of Mercury's magnetosphere. This compares with previous estimates, from spacecraft observations, of individual FTEs opening between 0.1–1% of Earth's polar cap (see summary by Fear et al, ). Factoring in the high repetition rate, Imber et al () concluded that FTEs could provide at least ∼30% of the flux transport needed to drive Mercury's substorm cycle, compared with less than 2% at Earth.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Since the size of Mercury's polar cap is estimated to be about 4–6 MWb (Alexeev et al, ), this would suggest that an individual FTE could open flux corresponding to ∼1–5% of the open flux content of Mercury's magnetosphere. This compares with previous estimates, from spacecraft observations, of individual FTEs opening between 0.1–1% of Earth's polar cap (see summary by Fear et al, ). Factoring in the high repetition rate, Imber et al () concluded that FTEs could provide at least ∼30% of the flux transport needed to drive Mercury's substorm cycle, compared with less than 2% at Earth.…”
Section: Introductionsupporting
confidence: 86%
“…We have applied arguments from a recent study into the flux content of flux transfer events at Earth (Fear et al, ) to Mercury's magnetosphere. Using a statistically‐determined mean flux rope radius for “large” Hermean FTEs (Imber et al, ), upper values for the magnetic perturbation due to the passage of the FTE flux rope as reported during a period of extreme solar wind driving at Mercury (Slavin et al, ) and making the assumption that, at its largest extent, the reconnection process could occur coherently along a single reconnection line across the entire dayside magnetosphere (12 hr in magnetic local time), we place a sensible upper limit for the total flux content of a large flux transfer event at Mercury to be ∼1 MWb.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations